2021
DOI: 10.1111/hsc.13320
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare access experiences of persons with MS explored through the Candidacy Framework

Abstract: Canada has one of the highest rates of multiple sclerosis (MS) in the world, affecting 1 in every 385 individuals. An estimated 11 Canadians are diagnosed with MS every day, typically in their early adult years (Bray et al., 2014). Individuals diagnosed with MS are faced with managing a complex neurodegenerative condition with a heterogeneous disease course and an array of varying symptoms (Becker et al., 2018). Prognosis is difficult to determine, although many individuals move to a progressive form of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…Occupational therapists, mental health providers and physiotherapists were the top HCPs whom participants needed to see but could not access. Encountering providers who lacked knowledge about MS and understood their situations was also a significant concern ( 19 ), echoed in a related qualitative study ( 20 ) and in a second qualitative study among moderately to severely affected individuals with MS in Germany ( 21 ). A recent survey of 1,190 persons, 75% of whom had MS, identified the influence of multidisciplinary teams on health outcomes and experiences as one of the top five research priorities ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapists, mental health providers and physiotherapists were the top HCPs whom participants needed to see but could not access. Encountering providers who lacked knowledge about MS and understood their situations was also a significant concern ( 19 ), echoed in a related qualitative study ( 20 ) and in a second qualitative study among moderately to severely affected individuals with MS in Germany ( 21 ). A recent survey of 1,190 persons, 75% of whom had MS, identified the influence of multidisciplinary teams on health outcomes and experiences as one of the top five research priorities ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Service users, though often desperate for care, were faced with a much more restricted range of offers of care and lack of clarity about how adjudications for their eligibility were made. The apparently low level of rejections of offers by service users, in contrast with some other studies ( Pétrin et al, 2021 ) is perhaps suggestive of a problem of under-supply of care rather than enthusiastic endorsement of the offers that were made or an acceptance that the offers aligned with their needs. Our findings also offer important insights into how the adjudications were made.…”
Section: Discussionmentioning
confidence: 54%
“…Overall, these findings add to understanding of the dynamic and recursive nature of candidacy ( Pétrin et al, 2021 ), among other things further challenging a view of candidacy as involving a linear series of “stages” – the seven features are each relevant in producing candidacy, but not necessarily in easily predictable ways. For policy and practice, our findings suggest that the pandemic exposed and amplified multiple challenges and structural inequalities in relation to mental healthcare provision and organisation of services that pre-dated COVID-19.…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that there would have been greater change seen if participants had been primarily cared for by family physicians; 12.3% of 324 respondents in a recent survey of Canadians living with MS indicated that they received the majority of their care from general practitioners, 4% received no care for their MS, while 8% received their MS care primarily from walk-in clinics, after-hours clinics and emergencies. [27]…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26] This may be evolving in Canada, as suggested by Petrin et al in 2021, where survey respondents expressed high levels of satisfaction with their healthcare providers around respectful communication and in shared decision making. [27] PwMS require decades of specialized neurologic care, with average life expectancy of one large Canadian cohort estimated to be approximately six years less than the general population. [28] A cross-sectional questionnaire study of 1,205 PwMS identi ed unmet needs for PwMS as changing and evolving as their disability progresses.…”
Section: Introductionmentioning
confidence: 99%